Mathematical Literacy of University Students in Solving Higher-Order Thinking Skills (Hots) Problems in Advanced Geometric Transformations - Lailatul Adinda Fitria; Nur Lail Feny Andiny; Refni Adesia Pradiarti; Lailatul Adinda Fitria; Nur Lail Feny Andiny (Jurnal MIPA dan Pembelajarannya, 2026)
This study aimed to analyze the mathematical literacy of university students in solving Higher-Order Thinking Skills (HOTS)-based problems on geometric transformations in an Advanced Mathematics course. A descriptive qualitative approach was employed, involving six participants selected through purposive sampling to represent high-, medium-, and low-ability groups. Data were collected using a written HOTS-based mathematics test and analyzed following the data analysis model of Miles, Huberman, and Saldaña. The findings indicate that students' mathematical literacy can be classified into three categories: (1) accurate and appropriate visual representations, (2) inaccurate visual representations, and (3) absence of visual representations. Students in the high-ability category successfully demonstrated all indicators of mathematical literacy, including problem comprehension, solution strategy development, mathematical representation, visualization, and logical reasoning. Students in the medium-ability category exhibited partial understanding but still experienced conceptual misunderstandings and weaknesses in visualization. In contrast, students in the low-ability category were unable to integrate symbolic and visual representations effectively and demonstrated deficiencies across nearly all mathematical literacy indicators. These findings suggest that visual representation is a key factor in successfully solving HOTS-based geometric transformation problems. Therefore, mathematics instruction should be designed using contextual, visual, and HOTS-oriented learning approaches to enhance university students' mathematical literacy.